PENGARUH KOMPETENSI INTERNAL AUDITOR, OBJEKTIVITAS INTERNAL AUDITOR DAN KEBERANIAN MORAL TERHADAP EFEKTIVITAS AUDIT INTERNAL DENGAN DUKUNGAN MANAJEMEN SENIOR SEBAGAI VARIABEL MODERASI - Rakhmat, Frizky Danu; Fadhilah, Novia; Sirajuddin, Betri (Balance : Jurnal Akuntansi dan Bisnis, 2019)
The formulation of the problem in this study was to know how the effect of internal Internal Auditor Competence, Internal Auditor Objectivity and Moral Courage on the Effectiveness of Internal Audit with Senior Management Support as Moderating Variables (Empirical Study on Banking in Lubuklinggau City, South Sumatera Province. The type of research used associative research. The data used primary data and secondary data. The population and sample in this study were 31 respondent in Lubuklinggau city. Data collection techniques were using interview techniques and questionnaires. The analysis technique used qualitative analysis and quantitative analysis. The result of this study indicated that internal auditor competencies gave significantly affect the effectiveness of internal audits, internal auditor objectivity gave significantly affect the effectiveness of internal audits, moral courage gaeve significantly affect the effectiveness of internal audits, senior management supported moderates internal auditor competence in a pure modertor on the effectiveness of internal audits, supported senior management moderates internal auditor objectivity by moderating moderator on the effectiveness of internal audit and senior management support moderating moral courage by moderating equations to the effectiveness of internal audits.